Articles of Agreement. (International Monetary Fund, 2020)
The Articles of Agreement of the International Monetary Fund were adopted at the United Nations Monetary and Financial Conference (Bretton Woods, New Hampshire) on July 22, 1944. They were originally accepted by 29 countries and since then have been signed and ratified by a total of 189 Member countries. As the charter of the organization, the Articles lay out the Fund's purposes, which include the promotion of "international monetary cooperation through a permanent institution which provides the machinery for consultation and collaboration on international monetary problems". The Articles also establish the mandate of the Organization and its members' rights and obligations, its governance structure and roles of its organs, and lays out various rules of operations including those related to the conduct of its operations and transactions regarding the Special Drawing Rights. The key functions of the IMF are the surveillance of the international monetary system and the monitoring of members' economic and financial policies, the provision of Fund resources to member countries in need, and the delivery of technical assistance and financial services. Since their adoption in 1944, the Articles of Agreement have been amended seven times, with the latest amendment adopted on December 15, 2010 (effective January 26, 2016). The Articles are complemented by the By-laws of the Fund adopted by the Board of Governors, themselves being supplemented by the Rules and Regulations adopted by the Executive Board.